Metasploit the penetration tester's guide - Kennedy, David 1982-; Aharoni, Mati; Kearns, Devon; O'Gorman, Jim (No Starch Press, 2025)
Metasploit: The Penetration Tester's Guide has been the definitive security assessment resource for over a decade. The Metasploit Framework makes discovering, exploiting, and sharing vulnerabilities quick and relatively painless, but using it can be challenging for newcomers.
Includes index
Keywords: Metasploit (Electronic resource); Computers -- Access control; Penetration testing (Computer security); Computer networks -- Security measures -- Testing; Ordinateurs; Accès; Contrôle; Tests d'intrusion